Treatment in a preventive cardiology clinic utilizing advanced practice providers effectively closes atherosclerotic cardiovascular disease risk‐management gaps among a primary‐prevention population compared with a propensity‐matched primary‐care cohort: A team‐based care model and its impact on lipid and blood pressure management. Issue 6 (5th June 2018) - Fentanes, Emilio; Vande Hei, Anthony G.; Holuby, R. Scott; Suarez, Norma; Slim, Yousif; Slim, Jennifer N.; Slim, Ahmad M.; Thomas, Dustin
Abstract : Background: Advanced practice providers (APPs) can fill care gaps created by physician shortages and improve adherence/compliance with preventive ASCVD interventions. Hypothesis: APPs utilizing guideline‐based algorithms will more frequently escalate ASCVD risk factor therapies. Methods: We retrospectively reviewed data on 595 patients enrolled in a preventive cardiology clinic (PCC) utilizing APPs compared with a propensity‐matched cohort (PMC) of 595 patients enrolled in primary‐care clinics alone. PCC patients were risk‐stratified using Framingham Risk Score (FRS) and coronary artery calcium scoring (CACS). Results: Baseline demographics were balanced between the groups. CACS was more commonly obtained in PCC patients ( P  < 0.001), resulting in reclassification of 30.6% patients to a higher risk category, including statin therapy in 26.6% of low‐FRS PCC patients with CACS ≥75th MESA percentile. Aspirin initiation was higher for high and intermediate FRS patients in the PCC ( P  < 0.001). Post‐intervention mean LDL‐C, non–HDL‐C, and triglycerides (all P  < 0.05) were lower in the PCC group. Compliance with appropriate lipid treatment was higher in intermediate to high FRS patients ( P  = 0.004) in the PCC group. Aggressive LDL‐C and non–HDL‐C treatment goals (<70 mg/dL, P  = 0.005 and < 130 mg/dL, P  < 0.001, respectively), were more commonly achieved in high‐FRS PCC patients. Median post‐intervention SBP was lower among intermediate and low FRS patients ( P  = 0.001 and P  < 0.001, respectively). Cumulatively, this resulted in a reduction in median post‐intervention PCC FRS across all initial FRS risk categories ( P  < 0.001 for all). Conclusions: APPs within a PCC effectively risk‐stratify and aggressively manage ASCVD risk factors, resulting in a reduction in post‐intervention FRS.